(untitled) (Homoeopathy for All, 2025)
Homoeopathy, a science known for its gentle healing and holistic approach, has come a long way in India from being introduced by foreign missionaries in the 19th century to being regulated and promoted by the Government of India in the 21st century. Today, under the dynamic leadership of Prime Minister Shri Narendra Modiji India is witnessing a powerful resurgence of traditional and integrative medicine systems, including Homoeopathy, through the Ministry of AYUSH. This article presents a reflection on the journey of homoeopathy in India, but more importantly, it looks ahead-with confidence and optimism-towards a future where homoeopathy plays a central role in the nation’s public health, research, education, and global outreach.